Cloning of self-major histocompatibility complex antigen-specific suppressor cells from adult bone marrow (The Rockefeller University Press, 1990)
We examined if suppressor cell clones may be established from adult bone marrow that contains a population of cells capable of specifically downregulating the immune response directed toward self-major histocompatibility complex (MHC) antigens. Freshly prepared adult C3H (H-2k) marrow cells were cultured in medium containing interleukin 2 (IL-2), IL-3, or a mixture of IL-2 and IL-3. After 7-10 d, cells grown in IL-3-containing medium were screened for their capacity to suppress cytotoxic T lymphocyte (CTL) generation against self-MHC antigens in allogeneic mixed lymphocyte cultures. Cells capable of suppressing anti- C3H CTL generation were cloned by limiting dilution. Several suppressor clones were established that exhibited strong suppression of anti-H-2k, anti-H-2Kk/Ik, and anti-H-2Dk CTL generation, but failed to suppress anti-H-2d and anti-H-2b responses. When tested in a skin allograft model, intravenous injections of these bone marrow-derived anti-self suppressor cells (2.5 x 10(7) cells) together with IL-3 induced prolongation of C3H skin allografts in anti-mouse lymphocyte serum- treated B6AF1 mice. Injection of IL-3 alone had no effect on allograft survival. Moreover, these cells failed to prolong B10.AKM skin allografts on B6AF1 recipients. Northern blot analysis showed that these cells express full-length transcripts of the T cell receptor (TCR) gamma gene, but not those of TCR alpha, beta, or delta genes. However, no rearrangement of gamma gene was observed by Southern blot analysis. Flow cytometric analysis revealed that bone marrow-derived suppressor cells are strongly positive for Thy-1 antigen but negative for CD3, CD4 (L3T4), and CD8 (Lyt-2) surface markers, and express only class I MHC antigens. Suppressor cells derived from adult bone marrow may play an important role in extrathymic induction of self-tolerance.